An Effective Online Learning for Listening Skill Subject: Students' Voice - Husain, Nurlaila; Ali, Sri Widyarti (Universitas Nurul Jadid, 2023)
This study aims to investigate the expectations of English Language Education students regarding effective online learning, with a focus on the listening subject. Qualitative research was conducted with 68 participants in the 2019 academic year, using online questionnaires to collect data. Results indicate that students anticipate clear communication, lecturer presence, an appropriate tone, and support from the online learning environment. They expect online courses to be challenging and offer opportunities for active learning, self-reflection, small group discussions, and practical application of theory. Positive social interactions are highly valued by learners, both online and offline. While time management and the home environment are concerns, participants’ express confidence in their ability to complete online exercises and learn independently with effective time management, the flexibility offered by online courses, and support from family and friends. Findings suggest that students have high expectations for their online learning experience and believe that they can achieve their goals with the appropriate resources and support.